2019
DOI: 10.3390/su11195531
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Public Transparency on Financial Performance: The Moderating Role of Political Embeddedness

Abstract: Corporate public transparency (CPT) is instrumental for companies to establish communications and trust with the public by disclosing and communicating information concerning corporate environmental and social impacts. However, it is still in dispute whether CPT can help promote corporate financial performance (CFP). This paper studied the moderating role of political embeddedness on the relationship between CPT and CFP. We investigate multiple hypotheses about the moderating roles of the political embeddednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 74 publications
3
32
0
Order By: Relevance
“…Producers and enterprises in China need to pay attention to China’s policy progress and governance philosophy so as to respond to governmental intentions to achieve sustainable legitimacy and preferential treatment from the government [ 45 ]. With the support of network analysis and quantitative text analysis, some hidden valuable information can be mined from publicly published policy documents, contributing to corporate strategic management and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Producers and enterprises in China need to pay attention to China’s policy progress and governance philosophy so as to respond to governmental intentions to achieve sustainable legitimacy and preferential treatment from the government [ 45 ]. With the support of network analysis and quantitative text analysis, some hidden valuable information can be mined from publicly published policy documents, contributing to corporate strategic management and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Ahdal, Alsamhi, Tabash, and Farhan (2020) analyzed the effect of corporate governance mechanisms on the financial version of GCC and Indian listed firms and confirmed that board accountability (BA) and audit committee (AC) has a trivial impact on organizational performance, as measured by Tobin's Q and ROE, while transparency and disclosure (TD) harm organizational performance, as measured by Tobin's Q. Li, Miao, Zheng, and Tang (2019) investigated the link between overall transparency and corporate performance, and they posited a negative relationship between general transparency and the implementation of companies. Using census data of 2018, they proved that this relationship is due to increased transparency decreasing the performance of companies in general.…”
Section: Literature Review Related Work-corporate Transparencymentioning
confidence: 99%
“…Similarly, transparency and disclosure (TD) have a minor negative impact on firms' performance as measured by Tobin's Q. Li, Miao, Zheng, and Tang (2019) reported a negative relationship between general transparency and company performance as per data from the 2018 census, the reason being that with increasing clarity, the company performance decreases (generally). Thus, Zarahazalose and Moneva (2017) posited that transparency and company performance is positively correlated, where transparency helps a company.…”
Section: Relationship Between Corporate Transparency and Firm Performancementioning
confidence: 99%
“…Among them, paper is considered to be a promising substrate for manufacturing environmentally friendly FHs due to its eco‐sustainability, renewability as well as low price. [ 20 ]…”
Section: Figurementioning
confidence: 99%